PERKEMBANGAN DAN PEMILIHAN PRIORITAS JENIS INDUSTRI HILIR TEH INDONESIA - ROHAYATI SUPRIHATINI (SOCA: Jurnal Sosial Ekonomi Pertanian)
The pusposes of this study are to understand development of tea down-stream industries inIndonesia and to select the priority of those industries type to be developed. ComparativePerforma Index (CPI) analysis and Eickenrode weighting method was applied. The resultsshowed that the development of tea down-stream industries in Indonesia in the 1998-2001period tend to increase. The typical of tea down-stream industries that could be prioritizedconsecutively for their development were as followed: (1) extract tea, (2)packing and bulkblack tea, and (3) ready to drink with tea aroma. Those mentioned industries, therefore,should get good facilities and services from the government in dealing with licensing, fundingand taxation.